THE PERCEPTION OF ACEH ISLAMIC SCHOLARS TOWARDS THE LEGALITY OF PREWEDDING PHOTOS - Rizki Mulya Nanda; Mutiara Fahmi; Sholihin, Riadhus (JURISTA: Jurnal Hukum dan Keadilan, 2025)
Prewedding comes from the English word which in Indonesian is a photo taken before the wedding. This means that all the processions that are carried out before the wedding and immortalised in a photo, then all these photos are prewedding photos. Prewedding photography is well known to many people. Prewedding photos are often used as mementos in the form of documentation, as is the case in walimah. Talking about walimah, of course we will talk about the accessories and makeup that adorn each room, one of which is a picture of a prewedding photo, where the bride and groom take a photo together, which is carried out before making ijab qabul or before the marriage contract. The background of this research is the existence of intimate scenes or poses that often violate Islamic norms, especially in the Aceh Besar area, and are contrary to Islamic law. This research aims to find out 1) the practice of prewedding photos in Aceh Besar; and 2) The perception of Aceh Besar scholars regarding prewedding photos. The research used in this paper uses Field Research (field research) and Library Research (literature). The results showed that the practice of prewedding photos in Aceh Besar begins with an introduction between the photographer and the prospective couple, and continues with an agreement on the cost of shooting. Then proceed to the shooting session. As for the perception of Aceh Besar scholars, it can be concluded that it is permissible as long as it does not violate Islamic law, and it can also be haram when prospective brides who are not yet legal as husband and wife do prewedding that involves khalwat (being alone without a legal bond), ikhtilat (mixing men with women), because it is close to adultery and violates Islamic norms.